Color Stability of Rhodium-Coated Archwire after Immersion in Mouthwashes - Sami Kadhum Al-Joubori; Sara M. Al-Mashhadany; Alaa Faleh Albo Hassan (Hindawi Limited, 2023)
Background. Is to evaluate the color stability of rhodium-coated aesthetic archwires after immersion in two types of mouthwashes (fluoridated and nonfluoridated), study the effect of immersion time, and to compare the effect of these solutions on color stability of the aesthetic archwires. Materials and Methods. 35 rhodium-coated aesthetic archwires were prepared and divided two halves, arranged in seven strips (each strip contains 10 wires) and immersed in Deionized water, Sidrazac and Biofresh solution. The measurements of the color have been carried out through a computed spectrophotometer based on Commission Internationale de I'Eclairage L∗a∗b∗system, and color variations (ΔE∗), color measurements were repeated 7 and 21 days after immersion in the solution. Statistical analyses include mean, standard deviation, minimum, maximum, and inferential statistics which include ANOVA and Tukey (HSD) for testing for any statistically significant differences in light reflection of the groups; t-test was used to test for differences in immersion time intervals. The significance level has been set at P≤0.05. Results. Both types of mouthwashes resulted in color changes in different degrees and a higher color instability amount has been noted with Sidrazac-fluoridated mouthwashes, The color change amount has been increased with the time being statistically higher in 3 weeks of immersion, while there is nonsignificant color change after immersion in the Biofresh mouthwash. Conclusion.Rhodium-coated archwire shows high color changes in Sidrazac-fluoridated mouthwashes and nonsignificant color change after immersion in the Biofresh mouthwash.